2014
DOI: 10.4103/2231-4040.126996
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive microparticulate drug delivery system of curcumin against Helicobacter pylori infection: Design, development and optimization

Abstract: The purpose of the present research was to develop and characterize mucoadhesive microspheres of curcumin for the potential use of treating gastric adenocarcinoma, gastric and duodenal ulcer associated with Helicobacter pylori. Curcumin mucoadhesive microspheres were prepared using ethyl cellulose as a matrix and carbopol 934P as a mucoadhesive polymer by an emulsion-solvent evaporation technique. Response surface methodology was used for optimization of formulation using central composite design (CCD) for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Curcumin is a natural active ingredient extracted from dry rhizome of the turmeric Curcuma genus plant, turmeric and Curcuma, with extensive pharmacological effects, low toxicity, and good tolerance, and due to its economic value, it has become a hot spot for exploration (8). Findings of studies focusing on curcumin have identified a wide range of pharmacological activities such as anti-inflammation, anti-oxidation, lipid, anti-virus, anti-infection, anticancer, anticoagulant, anti-liver fibrosis and atherosclerosis, low toxicity and few side effects (9)(10)(11)(12)(13). However, the effect of curcumin on NSCLC and the underlying molecular mechanism remains unclear.…”
Section: Curcumin Inhibits Cell Proliferation and Induces Apoptosis Omentioning
confidence: 99%
“…Curcumin is a natural active ingredient extracted from dry rhizome of the turmeric Curcuma genus plant, turmeric and Curcuma, with extensive pharmacological effects, low toxicity, and good tolerance, and due to its economic value, it has become a hot spot for exploration (8). Findings of studies focusing on curcumin have identified a wide range of pharmacological activities such as anti-inflammation, anti-oxidation, lipid, anti-virus, anti-infection, anticancer, anticoagulant, anti-liver fibrosis and atherosclerosis, low toxicity and few side effects (9)(10)(11)(12)(13). However, the effect of curcumin on NSCLC and the underlying molecular mechanism remains unclear.…”
Section: Curcumin Inhibits Cell Proliferation and Induces Apoptosis Omentioning
confidence: 99%
“…Studies are available pertaining to the determination of minimum inhibitory concentration (MIC) values of curcumin apart from documentation of its anti-quorum sensing and anti-efflux pump activities ( Bhawana et al, 2011 ; Mun et al, 2013 ; Ali et al, 2014 ; Packiavathy et al, 2014 ; Zorofchian Moghadamtousi et al, 2014 ; Pandit et al, 2015 ; Tyagi et al, 2015 ). While determining the MIC of curcumin against different bacterial isolates we faced difficulty in determining and interpreting the results possibly due to its insolubility in aqueous phase leading to formation of colored precipitate.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed the permanency of microparticles in the deepest layers of the mucosa for over 6 h [29]. [48,49] Proteins Gliadin Load acetohydroxamic acid [50]; amoxicillin [51]; clarithromycin [52]; dual therapy [53] and triple therapy [54] Gelatin Load amoxicillin [55,56] Chitosan Deliver dual therapy [57,58]; amoxicillin [17,59]; tetracycline [44]; Antibacterial properties of chitosan [46,60,61] Copolymers Deliver antibiotics (several systems with different mixture of polymers, summarised in [22]); probiotics [62]; phytomedicine [63][64][65][66] and antacids [67].…”
Section: Mucoadhesivenessmentioning
confidence: 99%